The Optimization of Blended Learning in Extensive and Intensive Reading Course - Musdalifah Ifah Rahman (MAJESTY JOURNAL, 2020)
This study aimed to describe 1) the application of Blended Learning in extensive and intensive reading subjects, and (2) the students’ perception of the application of blended learning. The subject of this study was the students of the English education department at the Muhammadiyah University of Enrekang. The data in this study were the activities of students and the lecturer in the teaching and learning processes and the students’ perception of the learning process in the classroom. The results showed that (1) the students and the lecturer were actively engaged in live learning and online conversation, and (2) the students had a positive perception of learning.